2012
DOI: 10.1038/ncb2532
|View full text |Cite
|
Sign up to set email alerts
|

Centralspindlin and α-catenin regulate Rho signalling at the epithelial zonula adherens

Abstract: The biological impact of Rho depends critically on the precise subcellular localization of its active, GTP-loaded form. This can potentially be determined by the balance between molecules that promote nucleotide exchange or GTP hydrolysis. However, how these activities may be coordinated is poorly understood. We now report a molecular pathway that achieves exactly this coordination at the epithelial zonula adherens. We identify an extramitotic activity of the centralspindlin complex, better understood as a cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
286
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 230 publications
(305 citation statements)
references
References 57 publications
17
286
2
Order By: Relevance
“…7 RhoA signaling is a master regulator of actomyosin cytoskeleton and thus has been implicated in a variety of morphogenetic processes. [31][32][33][34][35][36] While the role for active RhoA signaling in facilitating essential cellular processes has been wellestablished 9,[37][38][39][40][41] there are circumstances where RhoA signaling must be downregulated, either physiologically or pathologically to elicit a biological response. 41,42 Given the importance of the actomyosin cytoskeleton in positively regulating RhoA signaling, 7,[43][44][45] targeting actin-regulators such as Coronin 1B might be one of the approaches to achieve a precise spatiotemporal regulation of RhoA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 RhoA signaling is a master regulator of actomyosin cytoskeleton and thus has been implicated in a variety of morphogenetic processes. [31][32][33][34][35][36] While the role for active RhoA signaling in facilitating essential cellular processes has been wellestablished 9,[37][38][39][40][41] there are circumstances where RhoA signaling must be downregulated, either physiologically or pathologically to elicit a biological response. 41,42 Given the importance of the actomyosin cytoskeleton in positively regulating RhoA signaling, 7,[43][44][45] targeting actin-regulators such as Coronin 1B might be one of the approaches to achieve a precise spatiotemporal regulation of RhoA.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we immunolabelled for endogenous RhoA, as we previously found that the junctional localization of RhoA requires it to be active and thus can be used as a proxy for RhoA activity. 9 We studied this in confluent MCF-7 and Caco-2 cells, expressing either control or Coronin 1B siRNA (Fig. 3A, B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noren et al [39], Asnaghi et al [70] Cadherin-mediated suppression of RhoA activity is dependent on p190RhoGAP activation but no direct binding of cadherin and RhoA has been established Catenins 1) Wildenberg et al [41] p120-Catenin associates physically with intracellular domain of cadherins and also binds with p190RhoGAP which is essential for cell-cell adhesion 2) Ratheesh et al [71] a-Catenin (cadherin associated protein) binds to central spindle which in turn inhibits p190RhoGAP-B localization thus maintaining RhoA activation which is necessary for cellcell junctions in interphase epithelial cells 3) Bairukova et al [72] p190RhoGAP regulates adherens junction via p120-Catenin, thereby mediating vascular endothelial barrier protection Endothelial transcription factors…”
Section: How General Is the Impact Of P190rhogap On Tissue Differentimentioning
confidence: 99%